Effect of palm fiber volume fraction for enhancing the physical and mechanical properties of epoxy composites - Kartika Sari; Sunardi -; Yazid Zainur Isnen; Agung Bambang Setio Utomo; Parmin Lumban Toruan; Ampala - Khoryanton (Jurnal Polimesin, 2025)
Reinforcing materials such as fiber; are most widely used to give new properties to composites. This study investigates the effect of palm fiber (Arenga pinnata) volume fraction on the physical and mechanical properties of epoxy-based composites. Composite specimens with 0% and 2.5% fiber volume fractions were fabricated, maintaining a uniform thickness of 2 mm. The fabrication process involved fiber extraction, mixing with epoxy resin, and controlled curing. The physical properties assessed included density, porosity, and water absorption, while mechanical testing involved tensile and bending tests. The results demonstrated that the 2.5% fiber-reinforced composite exhibited improved properties compared to the 0% fiber composite. The density increased from 5.85 g/cm³ to 13.43 g/cm³, while porosity and water absorption rose slightly to 0.40% and 0.03%, respectively. In mechanical testing, the tensile strength increased from 2.64 MPa to 6.29 MPa, while strain improved from 1.06% to 4.59%. Young’s modulus, however, decreased from 2.49 MPa to 1.37 MPa, indicating enhanced flexibility. The bending stress increased from 6.35 MPa to 10.85 MPa, and deflection improved from 1.45 mm to 7.35 mm. These findings indicate that incorporating 2.5% palm fiber provides an optimal balance between strength and flexibility, making it a promising reinforcement for lightweight composite applications.